The Effect of Single or Combined Dietary Supplementation of Mannan Oligosacharide and Probiotics on Performance and Slaughter Characteristics of Broilers - Abdel-Raheem , Sherief M.; Abd-Allah, Sherief M.S. (International Journal of Poultry Science, 2011)
A feeding trial was conducted to investigate the effects of dietary supplementation of prebiotic (mannan oligosaccharide, MOS), Probiotic (Saccharomyces cerevisiae) and their combination (synbiotic) on growth performance, some carcass traits and meat quality in broilers. One hundred, one day-old broiler chicks (Avian 48), were randomly assigned to 4 dietary treatments (25 birds/treatment) for 6 weeks. Treatment groups were as follow: 1. Basal diet (control); 2. Basal diet plus Mannan-Oligosaccharide (MOS) (2 g of MOS/kg of the starter diets and 0.5 g/kg of the grower diets); 3. Basal diet plus probiotic (Saccharomyces cerevisiae) 3 g/kg diet and 4.Basal diet plus the combination of pre and probiotics (synbiotic). The final BW, weight gain, carcass yield percentage and immune organ weights were significantly (p<0.05) increased in probiotic and synbiotic supplemented broilers in comparison with the control and prebiotic groups. Meat from prebiotics supplemented broilers was more tender and juicy. Serum total cholesterol and triglycerides were significantly decreased in all dietary treatments compared with the control birds. Supplementation of broiler diets with pre, pro and synbiotics significantly improved body weight, weight gain and feed conversion, some carcass traits and meat quality, compared with the un-supplemented control. The feed conversion rate was significantly lower in synbiotic supplemented group. The results of the present study demonstrated that synbiotic as growth promoters appeared to be superior compared to use pre or probiotic alone in optimizing digestion to convert feed into body mass more efficiently and improve broiler chickens growth performance.